2013
DOI: 10.1186/1746-4269-9-77
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical assessment of plant resources of Banda Daud Shah, District Karak, Pakistan

Abstract: BackgroundThe Indigenous knowledge of plants is scientifically and culturally very significant. This paper elucidates the empirical findings of an ethnobotanical survey of Banda Daud Shah, District Karak, Pakistan.MethodsData collection was carried out from October 2011 to September 2012. Total twelve survey trips were made, three in each season. About 100 respondents were interviewed; most of them were aged people between 60–70 years. Interviews were conducted using structured questionnaire composed of variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
92
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 20 publications
15
92
1
Order By: Relevance
“…The current findings are consistent with the findings by different researchers in Ethiopia and elsewhere (Balcha Abera, 2014;Anteneh Belayneh et al, 2012;Getnet Chekole et al, 2015;Abiyu Enyew et al, 2014;Murad et al, 2013;Yared Yigezu et al, 2014). Different from the current findings, studies conducted elsewhere indicated that the root parts were frequently used in preparation of pharmacological substances to cure various human and livestock ailments (Mirutse Giday et al, 2009;Fisseha Mesfin et al, 2009;Haile Yinger et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current findings are consistent with the findings by different researchers in Ethiopia and elsewhere (Balcha Abera, 2014;Anteneh Belayneh et al, 2012;Getnet Chekole et al, 2015;Abiyu Enyew et al, 2014;Murad et al, 2013;Yared Yigezu et al, 2014). Different from the current findings, studies conducted elsewhere indicated that the root parts were frequently used in preparation of pharmacological substances to cure various human and livestock ailments (Mirutse Giday et al, 2009;Fisseha Mesfin et al, 2009;Haile Yinger et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings were reported in a study done in Jimma zone, Ethiopia (Yared Yigezu et al, 2014) and in Karak district, Pakistan, (Murad et al, 2013). The reasons were as a tradition, women generally not expected to appear in public or discourse with strange men both by the society and family (the husbands and the religious rules did not allow in most cases).…”
Section: Discussionsupporting
confidence: 85%
“…Use of other plant parts is as indicated in Figure 5. Latest findings in agreement with this study conducted in Ethiopia indicated that leaf used more than other parts (Megersa et al, 2013;Getaneh and Girma, 2014;Maryo et al, 2015), as well as in other countries such as Pakistan (Murad et al, 2013) and Uganda (Tugume et al, 2016), reported similar findings. Utilization of leaves for drug preparation may not cause detrimental effect on the plants compared to the root or whole plant collections (Megersa et al, 2013;Regassa, 2013;Abera, 2014;Maryo et al, 2015).…”
Section: Plant Parts Used For Medicinesupporting
confidence: 88%
“…Differences in medicinal plants knowledge among age groups was also reported in other studies (Gebrezgabiher et al, 2013;Tamiru et al, 2013;Yigezu et al, 2014;Chekole et al, 2015;Tugume et al, 2016). This might be attributed to the current expansion of education and health centers to kebele level which has resulted in the young generation focusing on modern medicines (Belayneh and Bussa, 2014) and advancement in science and technology has changed the social values and therefore, transformed the younger generation at a faster rate into the new tradition (Awas, 2007;Murad et al, 2013).…”
Section: Characteristics Of Respondentssupporting
confidence: 58%
“…There is a lack of knowledge about medicinal value of all the available plants in Pattoki despite the fact that the most diverse flora of Pakistan is present here. These plants can be used to fight against the emerging diseases of new age if there medicinal value is calculated by precise surveys of Pattoki (Ahmed et al, 2015;Ahmed et al ., 2014;Barkatullah et al, 2015;Bibi et al, 2014a;Bibi et al, 2014b;Ishtiaq et al, 2015;Murad et al, 2013;Rashid et al, 2015;Shah et al, 2016). It was evident from the fact that majority of plants are subtropical to tropical as Pattoki lies in the subtropical to tropical region of Pakistan.…”
Section: Discussionmentioning
confidence: 97%